Reprogramming Halomonas for industrial production of chemicals. (1st July 2018) - Chen, Xiangbin; Yu, Linping; Qiao, Guanqing; Chen, Guo-Qiang
Abstract: Halomonas spp. are able to grow under a high salt concentration at alkali pH, they are able to resist contamination by other microbes. Development of Halomonas spp. as platform production strains for the next-generation industrial biotechnology (NGIB) is intensively studied. Among Halomonas spp., Halomonas bluephagenesis is the best studied one with available engineering tools and methods to reprogram it for production of various polyhydroxyalkanoates, proteins, and chemicals. Due to its contamination resistance, H. bluephagenesis can be grown under open and continuous processes not just in the labs but also in at least 1000 L fermentor scale. It is expected that NGIB based on Halomonas spp. be able to engineer for production of increasing number of products in a competitive manner.